2021
DOI: 10.3390/healthcare9050563
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Intimate Partner Violence among Women in Sexual Unions: Is Supportive Attitude of Women towards Intimate Partner Violence a Correlate?

Abstract: Intimate partner violence (IPV) is predominant in sub-Saharan Africa (SSA), with nearly 40 percent of women reporting IPV at some point in time. In this study, we investigated whether a supportive attitude towards IPV is associated with past-year experience of IPV among women in sexual unions in SSA. This study involved a cross-sectional analysis of data from the Demographic and Health Survey (DHS) of 23 countries in SSA. Bivariate and multivariable binary logistic regression analyses were performed to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Questions from the modified version of the conflict tactics scale were used to assess these three variables [ 41 , 42 ]. Details of the questions, responses to the questions, and their categorization have been used in previous studies [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Questions from the modified version of the conflict tactics scale were used to assess these three variables [ 41 , 42 ]. Details of the questions, responses to the questions, and their categorization have been used in previous studies [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on data from the third China Women’s survey (SSCW3) in 2010, the study of Breckenridge et al [ 25 ] showed the gender differences and reported the lifetime prevalence of marital victims: psychological violence (female: 24.9%, male: 22.8%), physical violence (female: 5.5%, male: 2.5%) and sexual violence (female: 1.7%, male: 0.3%). Based on relevant data from the Demographic and Health Survey (DHS) of 23 countries, Aboagye et al [ 26 ] found that women who support IPV are more likely to experience IPV than women who reject IPV. However, based on the interview data of 3740 Hong Kong couples, and comparing the self-reports between partners, Chan [ 4 ] concluded that there is gender symmetry in the prevalence of IPV; that is, women are as violent as men, and most IPV behaviors are mutual and two-way.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This justification and acceptance of IPV may lead to the reduction in the rate at which women are likely to report and seek help, and may increase the risk of women experiencing more episodes of partner abuses in the future. Additionally, the women in SSA may feel that their intimate partners can abuse them due to deep-rooted patriarchal norms and beliefs, which reinforce community tolerance for IPV [ 12 ]. Also, IPV is internalized when people have supportive views regarding it, which increases the likelihood of future perpetration as well as relational and overt victimization and this could have accounted for the observed finding in our study [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the women in SSA may feel that their intimate partners can abuse them due to deep-rooted patriarchal norms and beliefs, which reinforce community tolerance for IPV [ 12 ]. Also, IPV is internalized when people have supportive views regarding it, which increases the likelihood of future perpetration as well as relational and overt victimization and this could have accounted for the observed finding in our study [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation